2020
DOI: 10.1111/hae.14102
|View full text |Cite
|
Sign up to set email alerts
|

The societal burden of haemophilia A. I – A snapshot of haemophilia A in Australia and beyond

Abstract: IntroductionFew studies, both in Australia and overseas, have examined the social impacts of living with haemophilia A (HA) or the economic costs associated with the disorder. The purpose of this paper is to examine the epidemiology and societal burden of people with HA (PwHA) in Australia, with a particular focus on men with this disorder.MethodsThe epidemiology and societal burden of HA in Australia, with a particular focus on men with this disorder, were assessed, using data available in the Australian and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
9
1
Order By: Relevance
“…[20][21][22][23] However, people with haemophilia still experience bleeds and joint disease to some extent, which can affect their day-today life. 24,25 Up-to-date knowledge on all reproductive phases in the current era of haemophilia treatment in addition to current research on the psychosocial impact of haemophilia is essential to ensure quality of haemophilia reproductive healthcare. We aimed to explore HCs perspective during preconception, pregnancy, delivery, and the postpartum period to assist clinicians in meeting the needs of HCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23] However, people with haemophilia still experience bleeds and joint disease to some extent, which can affect their day-today life. 24,25 Up-to-date knowledge on all reproductive phases in the current era of haemophilia treatment in addition to current research on the psychosocial impact of haemophilia is essential to ensure quality of haemophilia reproductive healthcare. We aimed to explore HCs perspective during preconception, pregnancy, delivery, and the postpartum period to assist clinicians in meeting the needs of HCs.…”
Section: Introductionmentioning
confidence: 99%
“…This information is partially outdated as the prospects of living with haemophilia still change favourably due to introduction of non‐replacement therapy and gene therapy. 20–23 However, people with haemophilia still experience bleeds and joint disease to some extent, which can affect their day‐to‐day life 24,25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the 2015 Australian Burden of Disease Study showed that there was a total of 227 disability-adjusted life years (DALY), 138 years lived with disability (YLD) and 89 years of life lost (YLL) in males from hemophilia (Brown et al, 2020b). This financial burden of the disease may be explained by the number of healthcare professionals involved in the care of patients with hemophilia A: hematologists, hemophilia nurses, social workers, physiotherapies, psychologists, psychotherapists, general practitioners, and a variety of complementary therapists (i.e., acupuncture or massage therapists) (Brown et al, 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…There are also some limitations in current study. First, since the prevalence of hemophilia is much lower in women than in men [20], the lack of inclusion of women with hemophilia in this study may result in selection bias. Second, individual dietary habits and physical activity intensity may be confounding factors affecting BTMs.…”
Section: Discussionmentioning
confidence: 99%